A Genome-wide Association Study Identifying RAP1A as a Novel Susceptibility Gene for Crohn's Disease in Japanese Individuals. (29th November 2018) - Kakuta, Yoichi; Kawai, Yosuke; Naito, Takeo; Hirano, Atsushi; Umeno, Junji; Fuyuno, Yuta; Liu, Zhenqiu; Li, Dalin; Nakano, Takeru; Izumiyama, Yasuhiro; Ichikawa, Ryo; Okamoto, Daisuke; et al.
Abstract: Background and Aims: Genome-wide association studies [GWASs] of European populations have identified numerous susceptibility loci for Crohn's disease [CD]. Susceptibility genes differ by ethnicity, however, so GWASs specific for Asian populations are required. This study aimed to clarify the Japanese-specific genetic background for CD by a GWAS using the Japonica array [JPA] and subsequent imputation with the 1KJPN reference panel. Methods: Two independent Japanese case/control sets (Tohoku region [379 CD patients, 1621 controls] and Kyushu region [334 CD patients, 462 controls]) were included. GWASs were performed separately for each population, followed by a meta-analysis. Two additional replication sets [254 + 516 CD patients and 287 + 565 controls] were analysed for top hit single nucleotide polymorphisms [SNPs] from novel genomic regions. Results: Genotype data of 4 335 144 SNPs from 713 Japanese CD patients and 2083 controls were analysed. SNPs located in TNFSF15 (rs78898421, Pmeta = 2.59 × 10 −26, odds ratio [OR] = 2.10), HLA-DQB1 [rs184950714, p meta = 3.56 × 10 −19, OR = 2.05], ZNF365, and 4p14 loci were significantly associated with CD in Japanese individuals. Replication analyses were performed for four novel candidate loci [ p <1 × 10 −6 ], and rs488200 located upstream of RAP1A was significantly associated with CD [ p combined = 4.36 × 10 −8, OR = 1.31]. Transcriptome analysis of CD4+ effector memory T cells from lamina propria mononuclear cells of CD patients revealed a significant association of rs488200 with RAP1A expression. Conclusions: RAP1A is a novel susceptibility locus for CD in the Japanese population.